Zaključevanje uvedbe množičnega vrednotenja nepremičnin - Smodiš, Martin (Geodetski vestnik, 2011)
This article describes the mass valuation system, which enables cost effectiveappraisal of many similar pieces real estate on a defined date with standardized procedures and mass valuation models. The key result of the system is a relatively accurate appraised market value, depending on the valuation models quality and the quality of real estate data needed for the value calculation. The Trial Value Determination and Notification Project is also described from the general valuation point of view. Valuation models improvement is indicated on the basis of market analyses and a study of property owners' complaints about trial value determination according to the mass valuation standards, which is one of the last steps in the implementationof the mass valuation system.
Keywords: mass valuation system; množično vrednotenje nepremičnin; modeli vrednotenja nepremičnin; nepremičnine; valuation models